Studies on reproduction in cattle. Part I. The periodicity and duration of oestrus - Anderson, J. (1936)
It has been observed that Zebu cattle in East Africa appear to exhibit a seasonal fertility, in that fertile matings tend to occur more particularly at a certain season of the year (unpublished results). It seemed that this apparent seasonal fertility could best be explained by assuming that conditions for the occurrence of oestrus and ovulation were more favourable at this time of the year than at any other. Considerable variation in the duration and intensity of oestrus is known to occur, and Hammond, working under experimental conditions, noted that in Britain the average duration of oestrus is longest in the summer months and shortest in the winter months.